Preliminary Study of Vitamin D Deficiency and Its Associated Risk Factors in Libya - Mahmud Abushhewa,; Abdulati Salem,; Abdusalam Mahmoud,; Ramzi Mohsen,; Embarka Aqila, (AlQalam Journal of Medical and Applied Sciences, 2024)
This study was conducted to investigate levels among the target population and its associated risk factors in Libya.A cross-sectional study was conducted to investigate level and its associated risk factors in Libya during 2022-2023. 192 serum samples were tested in private laboratories. A structured designated questionnaire was filled in containing all the relevant information. Descriptive analyses frequency and percent were measured for numerical data, number, and percent for qualitative data using SPSS version 22. The chi-square test and student t-test were used for the data analysis and to investigate the level of association among variables at the significance level of (p<0.05). The ratio of female to male included in this study was estimated to be (77.04%) and (22.96%) respectively. Our results reported mean average of level among male (15.59 mg/dl), while in female (11.45 mg/dl), the results reported sex based significant difference (p=.00009). The present study results reported an overall average (12.40 mg/dl) of level. Regarding the age categories, our results reported variable differences in the levels, however there is no statistically significant difference (p=0.894). The results showed that using supplements for hypovitaminosis did not significantly influence therapeutic outcomes. The mean average level among males was significantly higher than those in females; however, both levels in the two groups are in the deficiency category. Interestingly the group who received treatment of vitamin D, their level was lower than the group who did not receive treatment. أجريت هذه الدراسة لمعرفة مستوى فيتامين د بين السكان المستهدفين وعوامل الخطر المرتبطة به في ليبيا. أجريت دراسة مقطعية لمعرفة مستوى فيتامين د وعوامل الخطر المرتبطة به في ليبيا خلال الفترة 2022-2023. تم فحص إجمالي 192 عينة مصل في المختبرات الخاصة. تم ملء استبيان منظم مخصص يحتوي على جميع المعلومات ذات الصلة. تم قياس تكرار التحليلات الوصفية والنسبة المئوية للبيانات العددية والعدد والنسبة المئوية للبيانات النوعية باستخدام SPSS الإصدار 22. وتم استخدام اختبار مربع كاي واختبار الطالب t لتحليل البيانات وللتحقق من مستوى الارتباط بين المتغيرات في مستوى الأهمية P <0.05. قدرت نسبة الإناث إلى الذكور المشمولة في هذه الدراسة بـ (77.04%) و (22.96%) على التوالي. أبلغت نتائجنا عن متوسط مستوى فيتامين د بين الذكور (15.59 ملغم / ديسيلتر)، بينما لدى الإناث (11.45 ملغم / ديسيلتر)، أشارت النتائج إلى اختلاف كبير على أساس الجنس p=0.00. أظهرت نتائج الدراسة الحالية متوسطًا إجماليًا (12.40 مجم / ديسيلتر) لمستوى فيتامين د. فيما يتعلق بالفئات العمرية، أشارت نتائجنا إلى اختلاف المتغيرات في مستويات فيتامين د، ولكن لا يوجد فرق ذو دلالة إحصائية (P = 0.894). أظهرت النتائج أن استخدام مكملات فيتامين د لنقص الفيتامين لم يؤثر بشكل كبير على النتائج العلاجية. كان متوسط مستوى فيتامين د بين الذكور أعلى بكثير من نظيره لدى الإناث، ومع ذلك، فإن مستويات فيتامين د في المجموعتين تقع في فئة النقص. ومن المثير للاهتمام أن المجموعة التي تلقت العلاج بفيتامين د، كان مستوى فيتامين د لديها أقل من المجموعة التي لم تتلق العلاج. وتوصي هذه الدراسة بإجراء المزيد من الدراسات الوطنية الموسعة لتشمل المزيد من متغيرات البيانات